Reflexiones sobre la paz mundial - Jaguaribe, Helio (Estudios Internacionales, 1984)
The two superpowers are currently oscillating between two strategic visions, the predominance of which alternates according to internal political tendencies and the perception that each has of the other's behavior. This leads us to wonder whether there is a realistic course of action capable of leading the world in the direction of a stable peace while it is still possible to prevent a great war. In this work we argue that such a line of action can be conceived and implemented in a realistic way. To do this, it must first be recognized that only a truly effective and representative international authority will have the conditions to reinforce a stable peace and that, secondly, it must be recognized that any change in the current strategic stalemate must be initiated by those actors who are not the superpowers: in this case, the Europeans, and more specifically, the Germans.